Estudo químico de Bowdichia virgilioides (Fabaceae) na busca de inibidores seletivos de cisteíno peptidases - Silva, Taynara Lopes (2014)
This work describes the isolation of bioactive secondary metabolites of the plant species Bowdichia virgilioides in the search for selective inhibitors of cathepsins K, L and V. Cathepsins are enzymes that have as primary function the degradation of proteins in the lysosomes, and are also related to development of diseases such as osteoporosis, rheumatoid arthritis, atherosclerosis and various cancers. This dissertation describes the bioactivity-guided study of the ethanol extracts and fractions obtained from the stems and leaves of B. virgilioides through fluorimetric inhibition assay of the enzymes studied. The extracts of B. virgilioides were subjected to successive fractionations using different chromatographic techniques leading to several pure substances. The isolated substances had their structures elucidated by NMR uni- and bi-dimensional and mass spectrometry. The hexane and ethyl acetate fractions of stem afforded eleven substances: 2 triterpenes, lupeol and lupenona; the mixture of steroids β-sitosterol and stigmasterol; 1 ester derivative of trans pcoumaric acid; 1 furofuran lignan, syringaresinol; 1Benzofuran derivative, bowdenol; 1 coumestrol derivative, 8-methoxycoumestrol, and 3 isoflavones, 7,3'-dihydroxy-4'- methoxyisoflavone, 5,4'-dihydroxy-7'-methoxyisoflavone and 4-hydroxy-7-methoxyisoflavone. All compounds were tested on their ability to inhibit the enzymes at a concentration of 100μM. 8-Methoxycoumestrol showed inhibition superior to 70% for cathepsin V. The potency of this inhibitor was determined and the IC50 value was found to be 17.4 ± 1.0μM for cathepsin V. The ester derivative of trans p-coumaric acid also showed good inhibition above 70% for cathepsin L and V at a concentration of 50μg/mL. So, a series of 8 esters derived from p-hydroxybenzoic acid, p-coumaric acid, cinnamic and ferulic were prepared, and have been evaluated regarding their inhibitory activities of the cathepsins at a concentration of 100μM. n-Octyl pcoumarate ester showed the best percentage inhibition for the three enzymes. The constituents of the hexane fraction of leaves of B. virgilioides were analyzed using the techniques 1H NMR and GC-MS.